Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1910
DOI: 10.1037/h0073013
|View full text |Cite
|
Sign up to set email alerts
|

Dreams as a cause of symptoms.

Abstract: M UCH interest has been awakened during the past few years in the analysis of dreams and the psychology of the mechanism of dream formation. As is well known, Freud has been the pioneer in this field, and in his Traumdeutung has given his views to the world in a well-elaborated form. The principles of Freud's work have been too well illustrated in this country by Jones, Putnam, Brill, and Onuf to admit of any attempt on my part to describe them further.The object of this paper is less to discuss the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1912
1912
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Some of our NM dreams which have some associations with sex are at the same time much more closely related to and connected with other native drives, and many NM dreams are like soldiers' war dreams in not being related to sex at all. Our results are sharply opposed to Jones' claim (41,(73)(74)(75)(76)(77)(78)(79)(80)(81) that every NM dream represents some kind of sexual assault. The majority of our NM dreams have the appearance of not even being associated with sex in spite of the fact that we have arbitrarily used Jones' definition of the NM (41,(20)(21)(22)(23)(24).…”
Section: Section 6 Representative Examples Of the More Common Types O...contrasting
confidence: 99%
See 2 more Smart Citations
“…Some of our NM dreams which have some associations with sex are at the same time much more closely related to and connected with other native drives, and many NM dreams are like soldiers' war dreams in not being related to sex at all. Our results are sharply opposed to Jones' claim (41,(73)(74)(75)(76)(77)(78)(79)(80)(81) that every NM dream represents some kind of sexual assault. The majority of our NM dreams have the appearance of not even being associated with sex in spite of the fact that we have arbitrarily used Jones' definition of the NM (41,(20)(21)(22)(23)(24).…”
Section: Section 6 Representative Examples Of the More Common Types O...contrasting
confidence: 99%
“…Chideckel (9) believes that " Repeated tormenting dreams will cause even cortical injury in adults leading to cerebral lesions of a serious nature in later life," and that " Patients with heart disease and high blood pressure may be killed in their sleep by a terrifying dream." Walsh (74,398) found that the dream was the common cause of enuresis in the F-M, and Waterman (76) described a number of symptoms that were caused by dreams. Taylor described several examples of false recognition, hysterical paralysis and contractures, and conduct disorders which were the after-effects of dreams (69,(591)(592)(593)(594).…”
Section: Section 6 Representative Examples Of the More Common Types O...mentioning
confidence: 99%
See 1 more Smart Citation
“…In his classic article, “Pathogenic Dreams in Non‐Western Societies,” George Devereux () identifies a “widespread cultural conviction” that certain forms of negative dream experience are associated with the onset of physical illness. In other words, in many cultural settings, dreams are described as being “pathogenic.” This connection between certain kinds of dream experience and the onset of illness is not unique to indigenous societies; the Western psychoanalytic literature has long noted a connection between dreams—usually of a distressing nature—and the manifestation of subsequent somatic symptoms, generally assumed to be psychogenic in nature (see Bartemeier ; Kupper ; Leveton ; Waterman ).…”
Section: The Anthropology Of “Pathogenic Dreams”mentioning
confidence: 99%
“…Dr. Waterman (20) makes a short study of dreams as a cause of various symptoms in psychopathic maladies. He finds, as many psychopathologists have shown before him, that dreams may give rise to psychopathic disturbances.…”
mentioning
confidence: 99%